A History of Legal Exclusion: Labour Relations Laws and British Columbia’s Agricultural Workers, 1937–1975 - Jensen, Heather (Labour / Le Travail, 2014)
Access to labour relations legislation is generally seen as a prerequisite to unionization of agricultural workers in Canada. British Columbia is one of eight Canadian provinces that now include agricultural workers in provincial labour relations legislation. But agricultural workers were not always included. Although union organizing and strike activity were not unheard of in BC’s agricultural sector in the 1930s, the Industrial Conciliation and Arbitration Act of 1937 excluded agricultural workers. This exclusion followed a larger pattern of excluding agricultural workers from employment-related legislation. Agricultural workers continued to be excluded until the mid-1970s, when the efforts of NDP backbenchers persuaded their own government that agricultural workers ought to be included in provincial collective bargaining laws. As demonstrated in a brief overview of the two campaigns to unionize agricultural workers under BC’s labour relations legislation since 1975, although small numbers of workers have been able to form unions and achieve collective agreements under the legislative protections of the Labour Code, those collective bargaining relationships have thus far proven unstable and often short-lived.